Penggunaan Media Stem-Linktree Dengan Soal Cerita Terhadap Hasil Belajar Siswa - Wahyuni Suryaningtyas; Nabila Sailal Farah; Febriana Kristanti; Sandha Soemantri (MUST: Journal of Mathematics Education, Science and Technology, 2024)
This study aims to describe the effect of using STEM-Linktree media with story problems on the learning outcomes of seventh-grade students of SMP Maryam Surabaya. The type of research used is pre-experimental with a quantitative approach. The research design uses One Group pretest-posttest. The population in the study were all seventh-grade students of SMP Maryam Surabaya. The sample was selected using random sampling because of the homogeneous academic background. Data collection techniques in the study used pretest, posttest, and questionnaires. Data analysis techniques used were N-gain, One Sample T Test, and Paired Sample T Test. The study results showed that the One Sample T Test obtained t_table=1,729 < t_count=14,295; then H1 is accepted H0 is rejected. Similar results were obtained from the Paired Sample T Test obtained t_table=1,729 < t_count=14,163; then H0 is rejected. The analysis results indicated that the use of STEM-Linktree media with story problems had a significant effect on student learning outcomes. Students' responses to learning using STEM-Linktree media with story problems were highly positive, falling within the "very good" category, with an average score of 83,5%.